2020
DOI: 10.1016/j.bbagen.2020.129568
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium elicits alterations in mitochondrial morphology and functionality in C3H10T1/2Cl8 mouse embryonic fibroblasts

Abstract: Background: Cadmium is a widespread contaminant and a recognized carcinogen. We previously showed that the administration of low cadmium doses for 24 hours treatment to healthy C3H10T1/2Cl8 cells at the beginning of Cell Transformation Assay (CTA), up regulates genes involved in metal scavenging and antioxidant defense, like metallothioneines, Glutathione S transferases and heat shock proteins. Still, although most cells thrive normally in the following weeks, malignancy is triggered by cadmium and leads to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
6
5
0
Order By: Relevance
“…This is likely accomplished through a mitochondrial reorganization in a tightly crowded distribution around the nucleus, as shown by confocal microscopy analysis. A similar picture was previously observed in C3H cells treated with CdCl 2 for 24 h (Oldani et al 2020b). However, all the NADH produced by Cd-treated C3H10T1/2Cl8 cells was e ciently reoxidized on the electron transport chain.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…This is likely accomplished through a mitochondrial reorganization in a tightly crowded distribution around the nucleus, as shown by confocal microscopy analysis. A similar picture was previously observed in C3H cells treated with CdCl 2 for 24 h (Oldani et al 2020b). However, all the NADH produced by Cd-treated C3H10T1/2Cl8 cells was e ciently reoxidized on the electron transport chain.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, no autophagy activation was detected in the two foci, suggesting that the autophagy observed after cadmium administration for 24 h was part of the early mechanism of defense against this metal. Comparing data reported in this paper with those previously obtained on healthy C3H10T1/2Cl8 cells treated with CdCl 2 for 24 h (Oldani et al 2020b), we observe that each focus maintains some but not all the alterations observed in C3H10T1/2Cl8. This nding suggests that the different alterations did not originally occur in all treated cells, but that different cells reacted to CdCl 2 exposure in different ways.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations